Teaching Acts Performance Its Solutions For Second Grade Students Of SDLB E Bhina Putera Surakarta In 2013/2014 Academic Year - Karimah, Nur Azizah; , Drs. Najmuddin Zuhdi, M.Ag (2014)
In every teaching learning activity there are many problems that arise. It also occures to the Islamic education teacher in teaching learning process. Based on student's background, who has a disorder or emotional barriers and behavioral disabilities, and less able to adapt well to the environment. Absolutly it raises many problems when the teachers are teaching certain materials. This thesis entitles "Teaching Acts Performance Its Solutions for Second Grade Students of SDLB E Bhina Putera Surakarta in 2013/2014 Academic Year". The problems to be discussed in this study are, (1) what are the problems of teachers in teaching the prayer acts for the second grade students SDLB E Bhina Putera Surakarta, (2) and how are the solutions of Islamic education teachers to overcome the problems that arise in teaching acts performance. The purpose of this study is to determine the teacher's problem in teaching the acts performance for the second grade students SDLB E Bhina Putera Surakarta and the solutions of Islamic education teachers to overcome the problems that arise in teaching acts performance. The benefits of this research are (1) theoretically add insight to teachers of Islamic education, (2) the foundation for future researchers. And practical benefits of the research is to provide information and input to SDLB E Bhina Putera of Surakarta on Problems of Islamic education teachers in teaching. This type of research is qualitative research (Field Research), the object of this study is two-graders SDLB E Bhina Putera Surakarta and Islamic education teachers. To get the data in this study, the writer uses the method of observation, interviews, documentation. For analyzing data, the writer uses the descriptive qualitative analysis techniques. Based on this study, the writer concludes that the problems of teaching acts performance for the second grade students SDLB E Bhina Putera Surakarta arise from several factors, including problems arising from students, curriculum, facilities and infrastructure, and the environment around the student. Based on the problems, the teacher has many efforts solve the problems. These efforts are the teachers always admonish and give advice continuity to the students. To solve the less time in teaching acts performance lesson, the teacher provides additional hours outside of school hours. The problem of textbooks, the teacher writes the material on the board and the student record it. And efforts of Islamic education teachers related to student environment is by giving good example to the students and always give advice to them.